Crosslinking of Monomeric Fibrin by Factor XIIIa - Dardik, Beatriz N; Shainoff, John R (Thrombosis and Haemostasis, 1979)
The acceleration of crosslinking that accompanies transformation of fibrinogen to fibrin has been suggested to arise from the aggregation of the fibrinogen rather than a change in affinity for the crosslinking enzyme, factor Xllla. A test of the importance of aggregation has been obtained from studies on the effect of removing fibrinopeptide B from fibrinogen. Specific removal of fibrinopeptide B through reaction of human fibrinogen with copperhead venom procoagulant enzyme at low temperatures yields fibrin which dissolves on warming to 37° C and dissociates fully into monomers on dilution to a concentration below 0.2 mg/ml. When this fibrin and a fibrin lacking both fibrinopeptides A and B were compared at high concentrations above 2 mg/ml which favored a high degree of aggregation of both forms, they underwent crosslinking at similar rates that were approximately thirty two (25 ± 0.5) times faster than crosslinking of fibrinogen. However, at concentrations below 0.2 mg/ml, the fibrin lacking B alone underwent crosslinking at only one sixty-fourth of the rate of fibrin lacking both fibrinopeptides A and B. The relatively slow crosslinking in dilute solutions of the fibrin lacking fibrinopeptide B appeared due to the unique dissociation of this fibrin into monomers at low concentrations. As judged from both the rate of stable clot formation and the rate of formation of dimeric y-chains, crosslinking of the monomers did not differ from that of fibrinogen.